2019
DOI: 10.14391/ajhs.16.45
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Cooperation ICT Program Development Aimed at “Nutrition Improvement”

Abstract: To promote care planning that prevents the progression of care dependency among care service users by improving their nutritional conditions, we examined the status of ICT use for such planning and contents of care plans, involving 714 care managers throughout Japan. Based on the results, we propose an ICT program to prevent the progression of care dependency among care service users by improving their nutritional conditions through interprofessional collaboration, adopting the following approaches: 1) standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…In a previous study examining the status of using information and communication technology (ICT) in the process of creating care plans, the use rate was generally high, but it was also suggested that ICT did not function as a problem-solving tool to link assessment and care plans and share the latter with service providers (Fujio, Enomoto, Furukawa, et al, 2019).…”
Section: Servicesmentioning
confidence: 99%
“…In a previous study examining the status of using information and communication technology (ICT) in the process of creating care plans, the use rate was generally high, but it was also suggested that ICT did not function as a problem-solving tool to link assessment and care plans and share the latter with service providers (Fujio, Enomoto, Furukawa, et al, 2019).…”
Section: Servicesmentioning
confidence: 99%
“…4) Concerning cooperation for "improving nutrition", we proposed the necessity of organic cooperation by the standardization of assessment and utilization of ICT. 5) We further clarified the relationship between "food type" and independence of physical/mental functions in older people requiring nursing care for the realization of "nutritional improvement" in the local comprehensive care system in Japan. 6) In this study, we hypothesized that the "tooth condition", which affects the "food type", is related to the independence of mobility and cognitive functions of older people requiring nursing care and examined the hypothesis in the residents of special elderly nursing homes.…”
Section: ⅰ Introductionmentioning
confidence: 96%